Pengaruh Pelatihan Dan Sertifikasi Kompetensi Pegawai Terhadap Kinerja Pegawai PT Sido Sari Multifarm Semarang - Islam, Ahmad Saddam Satria; Wahono, Budi; Anwarudin Broto Suharto, Muhammad Khoirul (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Employees can show the same performance among each oyher by increasing knowledge and also deepening experience to maximize the achievement of each individual’s performance. This study aims to determine the effect of training and certification competency on employee performance at PT Sido Sari Multifarm Semarang simultaneously and partially, and to find the dominant variable. The type of research used is explanatory research. This research was conducted employee at PT Sido Sari Multifarm Semarang. The time for the research was carried out from March to July 2024. The population in this study were employee at PT Sido Sari Multifarm Semarang, totaling 30 people. While the sample size in this study was 30 respondents. Based on the research results, it is known that simultaneously the variables of training and certification competency affect employee performance at PT Sido Sari Multifarm Semarang. Partially or independently the variables of training and certification competency on employee performance at PT Sido Sari Multifarm Semarang. Keywords: Training, Certification Competency, Performance